The factors influencing audit quality and its impact upon judgement on materiality level - Ahmad Winanto; Blasius Fembriyanto Trisno Saputro (STIE Binaniaga, 2019)
The purpose of this study is to determine profesionalism, professional ethics and experience on audit quality and effect of auditor upon judgement of materiality level. Data has been obtained by survey questionnaires, which is completed by auditors who work at Registered Public Accountants, started from junior up to partner level. The number of auditors of this study were 103 auditors from 16 Public Accounting Firm, period of January – May 2015. Data analyzed using Structural Equation Modelling (SEM) variance on (Partial Least Square). The result of this study has shown that professionalism and professional ethics have significant and positive influenced the auditor’ judgment on materiality level. And audit quality has significantly and positively influenced the auditor’ judgment on materiality level. Experience has not positively influenced audit quality and auditor’ judgement on materiality level. Keywords: Professionalism, experience , professional ethics, audit quality and auditor judgment on materiality level.